2022
DOI: 10.3389/fnhum.2022.940759
|View full text |Cite
|
Sign up to set email alerts
|

Resting and TMS-EEG markers of treatment response in major depressive disorder: A systematic review

Abstract: Electroencephalography (EEG) is a non-invasive method to identify markers of treatment response in major depressive disorder (MDD). In this review, existing literature was assessed to determine how EEG markers change with different modalities of MDD treatments, and to synthesize the breadth of EEG markers used in conjunction with MDD treatments. PubMed and EMBASE were searched from 2000 to 2021 for studies reporting resting EEG (rEEG) and transcranial magnetic stimulation combined with EEG (TMS-EEG) measures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…EEG is another measure that can potentially be used to predict treatment response. For the prediction of response to treatment for MDD, many types of EEG measures have been examined, including resting EEG, sleep EEG, event-related potentials (ERPs) and transcranial magnetic stimulation-evoked EEG (TMS-EEG) [10][11][12] . Some EEG measures have been investigated both to help diagnose MDD and predict treatment response from both pharmacological treatment and other therapeutic interventions 13 .…”
Section: Introductionmentioning
confidence: 99%
“…EEG is another measure that can potentially be used to predict treatment response. For the prediction of response to treatment for MDD, many types of EEG measures have been examined, including resting EEG, sleep EEG, event-related potentials (ERPs) and transcranial magnetic stimulation-evoked EEG (TMS-EEG) [10][11][12] . Some EEG measures have been investigated both to help diagnose MDD and predict treatment response from both pharmacological treatment and other therapeutic interventions 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of TMS with EEG (TMS-EEG) has garnered interest as a tool to record immediate and downstream cortical responses following magnetically targeted stimulation [30]. Studies using TMS-EEG have demonstrated that fronto-midline Theta power and Theta connectivity show good potential for predicting responses to rTMS treatment for depression [31].…”
Section: Introductionmentioning
confidence: 99%